The Economies of Imperial China and Western Europe - O'Brien, Patrick Karl. author. aut Link
XIV, 121 p. 1 illus.
Keywords: This book is a critical interpretation of a seminal and protracted debate in comparative global economic history. Since its emergence, in now classic publications in economic history between 1997-2000, debate on the divergent economic development that has marked the long-term economic growth of China and Western Europe has generated a vast collection of books and articles, conferences, networks, and new journals as well as intense interest from the media and educated public. O’Brien provides an historiographical survey and critique of Western views on the long-run economic development of the Imperial Economy of China – a field of commentary that stretches back to the Enlightenment. The book’s structure and core argument is concentrated upon an elaboration of, and critical engagement with, the major themes of recent academic debate on the “Great Divergence” and it will be of enormous interest to academics and students of economic history, political economy, the economics of growth and development, state formation, statistical measurements, environmental history, and the histories of science and globalization.